Dispersal limitations and long‐term persistence drive differentiation from haplotypes to communities within a tropical sky‐island: Evidence from community metabarcoding. Issue 24 (8th October 2021) - Gálvez‐Reyes, Nancy; Arribas, Paula; Andújar, Carmelo; Emerson, Brent C.; Piñero, Daniel; Mastretta‐Yanes, Alicia
Abstract: Neutral theory proposes that dispersal stochasticity is one of the main drivers of local diversity. Haplotypes‐level genetic variation can now be efficiently sampled from across whole communities, thus making it possible to test neutral predictions from the genetic to species‐level diversity, and higher. However, empirical data is still limited, with the few studies to date coming from temperate latitudes. Here, we focus on a tropical mountain within the Transmexican Volcanic Belt to evaluate spatially fine‐scale patterns of arthropod community assembly to understand the role of dispersal limitation and landscape features as drivers of diversity. We sampled whole‐communities of arthropods for eight orders at a spatial scale ranging from 50 m to 19 km, using whole community metabarcoding. We explored multiple hierarchical levels, from individual haplotypes to lineages at 0.5, 1.5, 3, 5, and 7.5% similarity thresholds, to evaluate patterns of richness, turnover, and distance decay of similarity with isolation‐by‐distance and isolation‐by‐resistance (costs to dispersal given by landscape features) approaches. Our results showed that distance and altitude influence distance decay of similarity at all hierarchical levels. This holds for arthropod groups of contrasting dispersal abilities, but with different strength depending on the spatial scale. Our results support a model where local‐scale differentiation mediated by dispersal constraints, combined with long‐term persistence of lineages, is an important driver of diversity within tropical sky islands.